Adsorption of As(V) and P(V) by magnetic iron-based alginate-chitosan beads: Competitive adsorption and reduction mechanism of As(V) induced by Fe(II) - Sun, Siqi; Zeng, Huiping; Xu, He; Zhao, Weihua; Qi, Wei; Hao, Ruixia; Zhang, Jie; Li, Dong (Colloids and surfaces. A, Physicochemical and engineering aspects, 2023)
Assessing the adsorption competition between arsenate (As(V)) and phosphate (P(V)) is crucial due to their coexistence in water. This paper studied the competitive adsorption processes of As(V) and P(V) on magnetic iron-based alginate-chitosan beads by beaker experiments, simultaneously using XRD and FTIR techniques for characterization. In the single system, both As(V) and P(V) adsorption on M-IACBs followed the Langmuir model, with maximum adsorption capacities of 14.2 ± 0.4 mg g−1 and 18.5 ± 0.4 mg g−1, respectively. In the binary system, the competitive adsorption of As(V) and P(V) is a multilevel heterogeneous process well evaluated by the extended Freundlich and pseudo-second-order models. When loaded simultaneously, the adsorption of As(V) was more significant than that of P(V) (2.72 mg g−1 vs. 1.71 mg g−1). The desorption of P(V) was favored over As(V) during sequential loading, and the adsorption of P(V) was more influenced by pH compared to As(V). The adsorption affinity of the composites follows the order: As(V) < P(V) (for the single system) and As(V) > P(V) (for the binary system). Finally, changes in arsenic species were studied under anoxic aqueous solutions and oxygen-enriched air. In aqueous solutions, As(V) is reduced to the more toxic and mobile As(III) by Fe(II), and As(III) exhibits desorption-readsorption behavior. In oxygen-enriched air, As(V) undergoes electron transfer with Fe(II) and O2, resulting in the appearance of As(III), which can also be oxidized back to As(V). This study provides an objective and critical evaluation of the data regarding the use of Fe-based adsorbents in removing As(V), offering novel insights for designing such adsorbents. [Display omitted] •The adsorption affinity follows: arsenate < phosphate (single system) and arsenate phosphate > phosphate (binary system).•In anaerobic aqueous solution, As(V) is reduced to t As(III) by Fe (II) and is subject to desorption-readsorption.•In oxygen air, Fe(II) oxidizes, creating vacancies for Fe(II) (Fe(III) and an electron) to move, reducing As(V) to As(III).